Active surveillance of canine visceral leishmaniasis and american trypanossomiasis in rural dogs from non endemic area - Tome, Rozeani Olimpio [UNESP]; Gaio, Fernanda Conceição [UNESP]; Generoso, Diego [UNESP]; Menozzi, Benedito Donizete [UNESP]; Langoni, Hélio [UNESP] (Colégio Brasileiro de Parasitologia Veterinária, 2011)
A leishmaniose visceral canina (LVC) e a tripanossomíase americana são importantes zoonoses para a saúde pública que encontram no cão o principal reservatório doméstico para o homem. O trabalho procurou estimar a prevalência de anticorpos circulantes anti-Trypanosoma cruzi e anti-Leishmania spp., em amostras de cães provenientes da zona rural do município de Botucatu, SP. Durante a campanha de vacinação antirrábica canina da zona rural do município, foram coletadas 689 amostras de soro e processadas pela técnica de imunofluorescência indireta. Os testes sorológicos revelaram a ausência de anticorpos anti-Leishmania spp. e, na pesquisa dos anticorpos anti-T. cruzi, foram detectados 3 (0,4%) cães.

The canine visceral leishmaniasis (CVL) and american trypanosomiasis are important zoonoses in public health and dogs are the main domestic reservoir of the parasite for humans. The goal of this study was to estimate the prevalence of circulating antibodies anti-Trypanosoma cruzi and anti-Leishmania sp. in sera of dogs from the rural area of Botucatu, SP, Brazil. During the annual vaccination campaign against canine rabies in rural area, 689 blood samples were taken and processed by indirect immunofluorescent antibody test. The serological tests revealed the absence of antibodies anti-Leishmania spp., but anti-T. cruzi antibodies were detected in 3 (0.4%) dogs.
Vigilância da leishmaniose visceral e da tripanossomíase americana em cães de área rural indene
Keywords: Cães; doença de Chagas; imunofluorescência indireta; leishmaniose; Dogs; Chagas disease; indirect immunofluorescence; leishmaniasis